2020
DOI: 10.1108/jmp-10-2018-0446
|View full text |Cite
|
Sign up to set email alerts
|

Gamifying a situational judgment test with immersion and control game elements

Abstract: PurposeAssessment gamification, which refers to the addition of game elements to existing assessments, is commonly implemented to improved applicant reactions to existing psychometric measures. This study aims to understand the effects of gamification on applicant reactions to and measurement quality of situational judgment tests.Design/methodology/approachIn a 2 × 4 between-subjects experiment, this study randomly assigned 315 people to experience different versions of a gamified situational judgment test, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 28 publications
3
31
1
Order By: Relevance
“…Although nearly half of the articles reviewed are atheoretical, where theory is mentioned or used, we note a good balance of native HR and management theories (e.g., applicant reactions, person-environment fit) with external theories common to the GBA context (e.g., goal-setting, self-determination). The early atheoretical nature of research in this area is consistent with other reviews of GBA research [30,52], but emergent theories in the broader context show promise [33,35]. As with any emerging discipline, we acknowledge the natural progression from description and exploration to theory development.…”
Section: Treatment Of Theorysupporting
confidence: 71%
See 1 more Smart Citation
“…Although nearly half of the articles reviewed are atheoretical, where theory is mentioned or used, we note a good balance of native HR and management theories (e.g., applicant reactions, person-environment fit) with external theories common to the GBA context (e.g., goal-setting, self-determination). The early atheoretical nature of research in this area is consistent with other reviews of GBA research [30,52], but emergent theories in the broader context show promise [33,35]. As with any emerging discipline, we acknowledge the natural progression from description and exploration to theory development.…”
Section: Treatment Of Theorysupporting
confidence: 71%
“…Organizations use GBA to increase their attractiveness as an organization [20], to improve their applicant pool [12], and to identify applicants and employees with needed digital competencies [48]. For applicants, GBA informs individuals about potential careers [32] and offers a means to assess skills for a position in an engaging way [33].…”
Section: Introductionmentioning
confidence: 99%
“…Although several researchers have recently focused on the psychometric validation of GBAs (Kocadere & Çağlar, 2015;Landers, 2019), relatively fewer research attempts have explored the candidate experience (e.g., Georgiou & Nikolaou, 2020). Extant research has shown that game elements in employee selection promote perceptions of organizational technical sophistication (Landers et al, 2020), perceived assessment length, and test motivation (Collmus & Landers, 2019), and also reflect higher levels of perceived fairness and organizational attractiveness in comparison to traditional methods (Georgiou & Nikolaou, 2020).…”
Section: Applicant Reactions To Assessmentmentioning
confidence: 99%
“…When gamification was initially applied in marketing and information system designs, the empirical research focused predominantly on a few selected sectors in which technology had conventionally been associated with enhancing provision, such as education/learning, health/exercise and crowdsourcing (Koivisto and Hamari, 2019). In recent years, empirical research started to explore the impact of gamification on shaping individuals' perceptions toward the gamified objects and facilitating related behavioral changes across various contexts through different applications and designs (Cardador et al, 2017;Landers et al, 2020). For example, gamification was found to improve consumers' innovative product adoption (e.g.…”
Section: Contextualization Of Gamificationmentioning
confidence: 99%